0175 Shift Work and its Impact on Sleep, Alertness and Performance in Intensive Care Health Workers. (27th April 2018) - Ganesan, S; Magee, M; Stone, J E; Mulhall, M D; Collins, A; Howard, M; Lockley, S W; Rajaratnam, S; Sletten, T L
Abstract: Introduction: Shift work is associated with impaired alertness and neurobehavioral functioning due to sleep loss and circadian misalignment. This study investigated in intensive care doctors and nurses (1)the amount of sleep obtained between different shift types[n=48, 33.9 ± 9.8 years], and (2)alertness and performance during day and successive night shifts[n=35]. Methods: Total sleep between shifts was calculated from sleep diaries and wrist-worn actigraphs. The Karolinska Sleepiness Scale(KSS) and Psychomotor Vigilance Task(PVT) were administered at the start, middle and end of a day shift, and the first and final (3 rd, 4 th, or 5 th ) of several consecutive nights. Urine samples were collected for 24–48 h prior to and during the day, first and final night shift for assessment of the 6-sulphatoxymelatonin(aMT6s) rhythm. Results: Healthcare workers obtained an average of 6.5 ± 1.8h of sleep between consecutive night shifts(nurses 21:00-07:30h; doctors 20:00-09:00h) compared to 6.1 ± 1.1 h between standard day shifts(nurses 07:00-15:30h; doctors 08:00-21:00h) and 7.7 ± 1.4h between evening shifts(nurses 13:00-21:30h). Sleep was shortest (5.5 ± 1.2h) between an evening and a day shift the next morning, a shift transition frequently worked by nurses. For doctors and nurses, mean PVT reaction time (379.7 ± 95.7ms) and PVT lapses (3.7 ± 5.5) were significantly higher at the end of the first night shift compared to the end of the day shift (322.4 ± 39.0ms, 1.3 ± 2.0). KSS, PVT reaction time and PVT lapses were most impaired closer to aMT6s peak. KSS ratings were higher at the end of the first night shift (6.8 ± 1.8) compared to the last night (5.6 ± 1.9, p < .05). There were no differences between the first and last night shift in PVT reaction time or lapses. Conclusion: Evening-to-day transitions should be minimized as they provide limited opportunity for recovery sleep between shifts due to the early morning shift start. Despite short sleep between day shifts, alertness and performance remain most impaired during night shifts, particularly at the end of shift. While healthcare workers report more sleepiness on the first night shift compared to subsequent nights, objective performance is equally impaired across night shifts. Support (If Any): CRC for Alertness, Safety and Productivity.